(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2015)
In present study, immediate release solid dispersion formulation of Entacapone with various lipids was developed using spray drying method. Entacapone is indicated for the treatment of Parkinson’s disease (PD) as an adjunct to levodopa/carbidopa therapy. Based on the process feasibility and solubility of resulting spray dried powder, formulation ENSD10 was selected for characterization and analyzed for in vitro dissolution profiles in three different pH media. The particle size of Entacapone in spray dried formulation ENSD10 was drastically reduced down to d90 of 25.86µ against d90 of as such drug substance, i.e., 124.74µ. Analysis by differential scanning calorimetry showed that the percentage of crystallinity has been significantly reduced in formulation ENSD10.The optimized solid dispersion formulation (ENSD10) by spray drying method comprising drug to lipid to lipid carrier ratio of 0.5:1:3 (Entacapone: Gelucire 50/13: Compritol) enhanced solubility nearly 6.31 fold and 3.75 fold as compared to pure drug and spray drug alone, respectively. The rate of drug release from spray dried powder was significantly improved and found to be on higher side as compared to the drug release from as such drug and spray dried drug alone. The obtained results suggested that developed Entacapone along with lipid carrier mixture by spray drying method has promising potential for oral delivery and might be an efficacious approach for enhancing the therapeutic potential of active substance.